Novel addition-fragmentation agent in cationic photopolymerization - Gupta, Mukesh Kumar; Mehare, Rupali S.; Singh, Raj Pal (Polymer Bulletin, 2010)
The aim of present study is to examine the photo-initiation efficiency of N,N-dimethylacrylamide-based allylic ammonium salt as one component addition-fragmentation agent (cationic photoinitiator cum radical source) in free radical accelerated cationic polymerization. Novel addition-fragmentation agent (AFA), 2-(N,N-dimethylcarboxy-3-propenyl)(phenylcarbonyl-4-phenylene) dimethyl ammonium hexafluoroantimonate (DMPDA) was synthesized as cationic photoinitiator and its initiation efficiency was examined in polymerization of cyclohexene oxide (CHO), isobutyl vinyl ether (IBVE), and n-butyl vinyl ether (n-BVE) in CH(2)Cl(2) solvent at wavelength lambda > 290 nm. The rate of polymerization increases with the increase in initiator concentration and reaction time. The results demonstrate that DMPDA acts as an efficient photoinitiator (AFA) without use of radical source in free radical accelerated cationic polymerization.
Keywords: Addition-fragmentation agent; Ammonium salt; Benzophenone; Cationic polymerization; Onium salt; Photopolymerization